Mickey Mouse clubhouse. Mickey's great clubhouse hunt - Mendoza, Ashley; LaDuca, Rob.; Parkins, Howy.; Cook, Victor; Allwine, Wayne, 1947-2009; Anselmo, Tony.; Burton, Corey; Cummings, Jim, 1952-; Farmer, Bill.; MacNeille, Tress; Ryan, Will, performer; Taylor, Russi; et al. (Burbank, CA : Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
Mickey and his pals are planning the best springtime party ever - and you're invited! But the festivities are put on hold when Mickey's magical clubhouse mysteriously breaks into pieces and disappears with Minnie, Donald, Goofy, and Daisy inside!
Title from container.
Originally broadcast on television, 2006.
"Playhouse Disney."
"Disney DVD with Disney's FastPlay."
"High-flying adventure."
Bonus features: Never-before-seen episode "Donald's hiccups;" "The best Easter party ever" sing along song.
Keywords: Mickey Mouse (Fictitious character) -- Juvenile drama; Minnie Mouse (Fictitious character) -- Juvenile drama; Clubhouses -- Juvenile drama; Parties -- Juvenile drama; Television programs; Children's television programs; Animated television programs; Fantasy television programs; Action and adventure television programs; Video recordings for the hearing impaired; French language materials; Spanish language materials